2015
DOI: 10.17219/acem/27920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture in Simulated Microgravity on the Development of Mouse Embryonic Testes

Abstract: Background. All known organisms develop and evolve in the presence of gravitational force, and it is evident that gravity has a significant influence on organism physiology and development. Microgravity is known to affect gene expression, enzyme activity, cytoskeleton organization, mitotic proliferation and intracellular signaling. Objectives. The aim of the present study was to study some aspects of the development in vitro of mouse embryonic testes in simulated microgravity. Material and Methods. Testes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The cell cycle distribution and the size of the effect may explain its transient timing without a particular acceleration in the proliferation rate, thus allowing the recovery of a number of cells in samples exposed to s-microgravity for 48 hours. Other studies showed contrasting results with regard to the effects induced by s-microgravity, which was reported to not affect the viability and proliferation of primary mouse Sertoli cells 32 , to exert beneficial effects on both the survival of testis germ cells 33 and the proliferation of spermatogonial stem cells 34 , and to inhibit cell proliferation and cycle progression in mesenchymal stem cells 35 37 compared to the respective control cultures. These results are at least partially inconsistent with the findings of the present study, but most of the previous studies were performed using a rotary cell culture bioreactor that allows cells to aggregate and maintains cells in suspension conditions that are postulated to provide better nutrient and oxygen supply for cultured cells than control cells, even if this benefit was denied to inner cells in the aggregates 33 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The cell cycle distribution and the size of the effect may explain its transient timing without a particular acceleration in the proliferation rate, thus allowing the recovery of a number of cells in samples exposed to s-microgravity for 48 hours. Other studies showed contrasting results with regard to the effects induced by s-microgravity, which was reported to not affect the viability and proliferation of primary mouse Sertoli cells 32 , to exert beneficial effects on both the survival of testis germ cells 33 and the proliferation of spermatogonial stem cells 34 , and to inhibit cell proliferation and cycle progression in mesenchymal stem cells 35 37 compared to the respective control cultures. These results are at least partially inconsistent with the findings of the present study, but most of the previous studies were performed using a rotary cell culture bioreactor that allows cells to aggregate and maintains cells in suspension conditions that are postulated to provide better nutrient and oxygen supply for cultured cells than control cells, even if this benefit was denied to inner cells in the aggregates 33 .…”
Section: Discussionmentioning
confidence: 96%
“…More concordant results depict the effect of s-microgravity on tissue and cell structures. Indeed, according to the results of ex vivo and in vitro experiments, the testis cords appeared de-structured 33 , 42 and cytoskeleton disorganization became evident during s-microgravity exposure 43 – 47 . As expected and consistent with previously published results 26 , transient microtubule disorganization was evident in our cell model after 24 h of exposure to s-microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…S4). Increased proliferation and cell viability, and lack of testicular cord formation have been reported under low gravity culture [27].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several studies indicated that mammalian cells are able to perceive gravitational force, even if not "mechano-sensitive cells", and respond to the changes of gravitational force [11][12][13][14]. Among them, male germ cells have been revealed to be sensitive to changes of gravitational force [15][16][17][18][19][20][21]. Our group focused the attention on TCam-2 cells, derived from a seminoma lesion, that through their malignant transformation, maintain at least partially the phenotypic and molecular features of their normal counterpart [22][23][24].…”
Section: Introductionmentioning
confidence: 99%